Development of Defect-Free Asymmetric Polysulfone Membranes for gas separation using response surface methodology - Ismail, Ahmad Fauzi; Lai, P. Y. (Elsevier, 2004)
This paper reports the preparation of defect-free asymmetric membranes through the manipulation of membrane fabrication variables, including polymer concentration, solvent ratio (ratio of less volatile solvent to more volatile solvent), forced-convective evaporation time and casting shear rate. Main effects and interaction effects of these variables on membrane structure and performance were investigated by using factorial design and response surface methodology in order to optimize membrane formation process. According to the results of this study, an essentially defect-free skin layer with skin thickness in the range of 6590â€“11330Ã… was prepared for asymmetric polysulfone membranes. Selectivity of these membranes was relatively higher as compared to conventional membranes; some of them even surpassed the intrinsic selectivity. Therefore, optimal processing conditions can be developed to prepare defect-free asymmetric membranes for gas separation.